Deep rTMS Mitigates Behavioral and Neuropathologic Anomalies in Cuprizone-Exposed Mice Through Reducing Microglial Proinflammatory Cytokines - Yang, Liu; Su, Yawen; Guo, Fannv; Zhang, Handi; Zhao, Yinglin; Huang, Qinjun; Xu, Haiyun (Frontiers in Integrative Neuroscience, 2020)
In comparison to conventional rTMS, theta burst stimulation is stronger and more effective as a brain stimulation approach within short periods of time. Although this deep rTMS technique is being applied in treating neuropsychiatric disorders, few animal studies have attempted to clarify the neurobiological mechanisms underlying its beneficial effects. This animal study examined effects of deep rTMS on the cuprizone-induced neuropathologic and behavioral anomalies and explored the underlying mechanism. Adolescent male C57BL/6 mice were fed a rodent chow without or with cuprizone (CPZ; 0.2% w/w) for 5 weeks. Another two groups of mice were subjected to deep rTMS or sham rTMS once a day during weeks 2-5 of the CPZ-feeding period. The behaviors of all mice were assessed after withdrawal of CPZ prior to neuropathological and immunological analyses. Compared to CNT group, mice in CPZ and CPZ+Sham groups showed deficits in social recognition and spatial working memory as well as anxiety-like behavior, in addition to myelin breakdown and OL loss in corpus callosum, caudate putamen, cerebral cortex, and hippocampus of the brain. Deep rTMS effectively reduced behavioral anomalies and blocked myelin breakdown and OL loss in CPZ-fed mice. In addition, it also dampened microglia activation at lesion sites and rectified cytokines levels (IL-1β, IL-6, and IL-10) in CPZ-affected regions. The most significant effect was seen in cerebral cortex where alleviated neuropathology co-existed with less microglia activation and higher IL-10 level. These data provided experimental evidence for the beneficial effects of deep rTMS in CPZ-fed mice and revealed a neurobiological mechanism of the modality.